Mitigate Wildfire Impacts on Drinking Water Quality and Operations. Issue 5 (3rd June 2021) - Tran, Tiffany; Baribeau, Hélène; Sullivan, Laurie
Abstract : The 2020 wildfire season set records in the United States, particularly in California, and the effects of those fires can be felt by water utilities throughout their water treatment and distribution systems. In response to these destructive events, the California Urban Water Agencies held a workshop on wildfire impacts to share best management practices, adaptation resources, and lessons learned.